A Blockchain Based Data Monitoring and Sharing Approach for Smart Grids - Yanhan Yang; Mingzhe Liu; Qin Zhou; Helen Zhou; Ruili Wang (IEEE Access, 2025)
With the development of science and technology, human beings cannot live without electricity. The introduction of smart grid systems brings new ideas to break the shackle of existing electricity systems. This paper proposes a mechanism with data monitoring and sharing capabilities based on the consortium blockchain, realizing comprehensive monitoring of smart devices, and promoting the effective sharing of electrical data in smart grids. When a smart device is out of order, the smart contract connected to it will be triggered, and the users can check the running status through the smart phone. This approach allows nodes in the consortium blockchain to request transactions, using the prepaid payment smart contract with time-lock script to protect the consumer right of request nodes. In addition, we use a $(t,n)$ -threshold secret sharing scheme to realize multiparty sharing of electrical data. Paillier encryption arithmetic is used to guarantee the confidentiality of messages in node transaction.